The Role of Price Perception and Perceived Risk in Shaping Online Food and Beverage Purchase Decisions - Alfira, Hana; Chaerani, Gita Mutiara Annisa (ProBisnis : Jurnal Manajemen, 2025)
This study investigates the impact of price perception and perceived risk on consumers' online purchasing decisions for food and beverage. The population in this study consists of consumers who purchase food and beverages online through platforms such as GoFood, GrabFood, and ShopeeFood. The sample consists of 120 respondents chosen through purposive sampling, and the analysis was carried out using multiple linear regression in SPSS. The research shows that purchasing decisions are influenced by both price perception and perceived risk, both partial and simultaneous. This research provides insights for food and beverage sellers using GoFood, GrabFood, and ShopeeFood platforms, suggesting that implementing appropriate pricing strategies and minimizing perceived risks can potentially influence purchasing decisions.